Generic qualitative dissertations in counselor education: A content analysis. (5th February 2023) - Waalkes, Phillip L.; DeCino, Daniel Andrew; LeBlanc, Joe; Phelps‐Pineda, Monica Maria; Somerville, Tiffany; Flynn, Stephen V.
Abstract: We conducted a content analysis of generic qualitative counseling dissertations (GQR; N  = 70), examining their methodological justifications, coherence, and trustworthiness. Dissertations authors often presented vague methodological justifications. Findings have implications for constructing methodological justifications, integrating relevant literature, and awareness of how GQR compares to other qualitative methodologies.